2011
DOI: 10.1016/j.aller.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The prevalences of allergic diseases in rural and urban areas are similar

Abstract: According to our results, atopic diseases can be considered frequent in Konya, history of atopy in the family is the most predictive factor and the effects of rural or urban factors are not obvious in atopic disease development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
3
16
2
Order By: Relevance
“…This is not consistent with other studies [18,19]. Passive tobacco smoking and exposure to outdoor dust and smoke were significant risk factors in the prevalence of asthma but had no significant effect on the need for hospital admission in our study, whereas other studies showed that exposure to smoke increased the severity of asthma and the need for hospital admission [14,20]. These differences between our study and others may be due to the small number of cases in our study, and ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫عرش‬ ‫التاسع‬ ‫املجلد‬ ‫السادس‬ ‫العدد‬ the small numbers hospitalized, which may have affected the likelihood of findings significant differences.…”
Section: Risk Factors For Hospitalizationcontrasting
confidence: 99%
See 2 more Smart Citations
“…This is not consistent with other studies [18,19]. Passive tobacco smoking and exposure to outdoor dust and smoke were significant risk factors in the prevalence of asthma but had no significant effect on the need for hospital admission in our study, whereas other studies showed that exposure to smoke increased the severity of asthma and the need for hospital admission [14,20]. These differences between our study and others may be due to the small number of cases in our study, and ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫عرش‬ ‫التاسع‬ ‫املجلد‬ ‫السادس‬ ‫العدد‬ the small numbers hospitalized, which may have affected the likelihood of findings significant differences.…”
Section: Risk Factors For Hospitalizationcontrasting
confidence: 99%
“…In our analysis asthma was more common among male children, which is in agreement with other studies [11,12,14]. Some studies show no significant difference between males and females [15].…”
Section: Risk Factors For Hospitalizationsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of a higher prevalence of self-reported AR in the rural area than in the urban area investigated in the present study are similar to those in Korea, the Philippines, and Turkey; however, the higher prevalence of AR in urban areas was reported in Europe and Africa as well as West Germany after reunification (Table 6). 18,19,20,21,22,23,24,25 This difference in the rural and urban areas in the present study may be due to several factors. In particular, interview response rates was lower in the rural area (75.9%) than in the urban area (81.5%), which possibly led to underreporting and underdiagnosis of AR in the rural area.…”
Section: Discussionmentioning
confidence: 52%
“…We speculated that the apparent increase was primarily due to heightened awareness of atopic diseases among the public and health care providers. In another survey from Turkey, researchers found that the risk of progression to asthma and atopic diseases was higher in families in which the paternal educational level was low and that the sensitivity and awareness of these disorders may cause the prevalence to appear higher than it was 24. A cross-sectional survey among otolaryngologists in Mainland China has recently demonstrated that while most of the otolaryngologists (61%) diagnosed AR based on medical history and nasal examination, only 35% of the otolaryngologists used skin prick tests or specific IgE serum tests 31.…”
Section: Discussionmentioning
confidence: 99%